(untitled) (Wallingford, Oxforshire, UK,Cambridge, MA, 2004)
Many international forus have identified the need for comprehensive, transparent, scientific methods for the pre-release testing and post-release monitoring of transgenic plants to ensure their environmental safety and sustainable use. There is also wide recognition that the regulatory and scientific capacity for conducting assessments needs to be strengthened worldwide.
Keywords: Crops,Transgenic plants,Corn,Cây trồng; Genetic engineering,Environmental aspects,Risk assessment,Genetic engineering,Công nghệ gen,Khía cạnh môi trường